A Study of Thermoelectric Performance of TlGaSe2 Layered Dichalcogenides from First-Principles Calculations: Vacancy Defects Modeling and Engineering - Caydasi, Murat; Mintas, Mehmet Fatih; Chumakov, Yurii M.; Volz, Sebastian; Cengiz, Asuman; Seyidov, MirHasan Yu (Wiley-V C H Verlag Gmbh, 2022)
Herein, the thermoelectric performance of TlGaSe2 ternary layered dichalcogenides is evaluated by applying ab initio density functional theory calculations combined with Boltzmann's transport equation. A novel approach to design the intrinsic structural defects via Se-anion vacancies in unit cell has been developed. Two kinds of Se-vacancy defects in host TlGaSe2 crystal lattice are engineered: the single vacancy defect induced intrinsically in the unit cell (1x1x1) and in the supercell lattice (1x1x4). It is found that the electrical transport properties and thermoelectric efficiency of this semiconductor could be significantly altered by introducing Se-vacancy states into crystalline structure. In addition, simulation shows that inclusion of Se-vacancy defects significantly improves the thermoelectric efficiency as well as the thermoelectric power factor and figure of merit (ZT) values of this compound. Additionally, the thermoelectric performance of TlGaSe2 is estimated by means of the electronic fitness function calculations in the valence and conduction edges. The results demonstrate that TlGaSe2 with introduced Se-vacancies may be a perspective material for thermoelectric applications.
Keywords: 2D ternary chalcogenides; Boltzmann transport equation; density functional theory; electronic thermal conductivity; thermoelectrics